Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Pada Pembelajaran Biologi Materi Sistem Peredaran Darah Manusia di Kelas VIII SMP GPdI Berea Tondano - Yubellian Yoru; Masje Wurarah; MEity N. Tanor (LPPM Politeknik Pratama, 2024)
The learning process at SMP GPDI Berea Tondano is considered to be still not optimal which results in low student learning outcomes. For this reason, the purpose of this research is to improve student learning outcomes by applying the jigsaw type cooperative model. This reseaarch is an action research (PTK) subject in this study, namely all student in class VIII SMP GPDI Berea Tondano semester 1 of the 2021/2022 academic year as many as 17 people. The instruments used in this study were observation sheets and learning achievement test. Based on the analysis of student learning outcomes individually in cycle I, a persentage of 50,76% was obtained, and the percentage in cycle II was 80,58%, while classically in cycle I, a percentage was obtained 29, 14% and the percentage in cycle II was 82,32%, then the results of activity observation student learning in cycle I obtained a percentage of 60,71% and a percentage of cycle II 92,85%. The results of the study concluded that the application of the jigsaw cooperative type can improve student learning outcomes in science subjects which have increased in cycle II.